PENGEMBANGAN PENILAIAN PEMBELAJARAN AKUNTANSI KONTEKSTUAL BERBASIS LESSON STUDY DI SMA - Suyatmini, Suyatmini; Sutama, Sutama; Rohmah, Wafrotur; Asmawati, Titik (Jurnal Pendidikan Ilmu Sosial, 2019)
This study aims to (1) analyze and describe the assessment of accounting learning conducted by high school teachers in Surakarta City-Central Java. (2) the development of lesson study based contextual accounting learning assessment. This study uses the research and development approach. Research subjects of high school accounting teachers in Surakarta City. Methods of data collection, interviews, observation and documentation. Data analysis techniques use interactive analysis which includes data collection, data reduction, data display and verification. The validity of the data uses triangulation methods and sources. The results of the study indicate that the judgments carried out include affective assessment, cognitive assessment and psychomotor assessment. The evaluation of accounting learning in high school of Surakarta City for affective aspects are using two ways, namely the assessment of spiritual attitudes competency and social attitudes assessment. Assessment of spiritual attitudes uses self-assessment techniques. Social attitude competency assessment uses observation techniques, self-assessment journals, and peers. Assessment of accounting learning for cognitive aspects using tests and assignments. There are three learning assessments for psychomotor aspects, namely project appraisal, performance, and portfolio. Development is carried out on assessment instruments for both affective, cognitive, and psychomotor aspects. The development of the affective aspect is carried out by the spiritual attitude competency assessment instrument and the social attitude competency assessment instrument with observation techniques. The development of cognitive aspects is carried out on the instrument for assessing cognitive aspects and the timing of the implementation of cognitive instruments. Development of psychomotor aspects is carried out on the implementation of psychomotor instruments.